math stuff

- hey sam, what you doing?
- 2/3( 4x - 2) = 2/3( x - 4) = 6x + 4 /3 = 2 + x - 4 /3 =6x + 4 = 2 + x - 4 = 6x + x = 2 - 4 + 4 = 7x = 2 = 7x/7 = 2/7 x = 0.28
- I just solved a really hard math question, look
- I think you did it wrong. You added instead of multiplying when you distributed and you didn't change signs when you moves the numbers to other sides.
- 2/3( 4x - 2) = 2/3( x - 4) = 6x + 4 /3 = 2 + x - 4 /3 =6x + 4 = 2 + x - 4 = 6x + x = 2 - 4 + 4 = 7x = 2 = 7x/7 = 2/7 x = 0.28 2/3( 4x - 2) = 2/3( x - 4) = 6x + 4 /3 = 2 + x - 4 /3 =6x + 4 = 2 + x - 4 = 6x + x = 2 - 4 + 4 = 7x = 2 = 7x/7 = 2/7 x = 0.28 2/3( 4x - 2) = 2/3( x - 4) = 6x + 4 /3 = 2 + x - 4 /3 =6x + 4 = 2 + x - 4 = 6x + x = 2 - 4 + 4 = 7x = 2 = 7x/7 = 2/7 x = 0.28 2/3( 4x - 2) = 2/3( x - 4) = 6x + 4 /3 = 2 + x - 4 /3 =6x + 4 = 2 + x - 4 = 6x + x = 2 - 4 + 4 = 7x = 2 = 7x/7 = 2/7 x = 0.28 2/3( 4x - 2) = 2/3( x - 4) = 6x + 4 /3 = 2 + x - 4 /3 =6x + 4 = 2 + x - 4 = 6x + x = 2 - 4 + 4 = 7x = 2 = 7x/7 = 2/7 x = 0.28
- Oh. Can you show me
- Instead of adding the 2/3 you multiply it into the brackets, so it becomes...
- 2/3( 4x - 2) = 2/3( x - 4) = 6x + 4 /3 = 2 + x - 4 /3 =6x + 4 = 2 + x - 4 = 6x + x = 2 - 4 + 4 = 7x = 2 = 7x/7 = 2/7 x = 0.28 2/3( 4x - 2) = 2/3( x - 4) = 6x + 4 /3 = 2 + x - 4 /3 =6x + 4 = 2 + x - 4 = 6x + x = 2 - 4 + 4 = 7x = 2 = 7x/7 = 2/7 x = 0.28 2/3( 4x - 2) = 2/3( x - 4) = 8x + 4/ 3 = 2x - 8/ 3 = 8x + 4 = 2x - 8
- When you move the numbers to other sides, the sign changes. You forgot to do that. Now it would become...
- 2/3( 4x - 2) = 2/3( x - 4) = 6x + 4 /3 = 2 + x - 4 /3 =6x + 4 = 2 + x - 4 = 6x + x = 2 - 4 + 4 = 7x = 2 = 7x/7 = 2/7 x = 0.28 2/3( 4x - 2) = 2/3( x - 4) = 6x + 4 /3 = 2 + x - 4 /3 =6x + 4 = 2 + x - 4 = 6x + x = 2 - 4 + 4 = 7x = 2 = 7x/7 = 2/7 x = 0.28 2/3( 4x - 2) = 2/3( x - 4) = 6x + 4 /3 = 2 + x - 4 /3 =6x + 4 = 2 + x - 4 = 6x + x = 2 - 4 + 4 = 7x = 2 = 7x/7 = 2/7 x = 0.28
- 2/3( 4x - 2) = 2/3( x - 4) = 6x + 4 /3 = 2 + x - 4 /3 =6x + 4 = 2 + x - 4 = 6x + x = 2 - 4 + 4 = 7x = 2 = 7x/7 = 2/7 x = 0.28 2/3( 4x - 2) = 2/3( x - 4) = 6x + 4 /3 = 2 + x - 4 /3 =6x + 4 = 2 + x - 4 = 6x + x = 2 - 4 + 4 = 7x = 2 = 7x/7 = 2/7 x = 0.28 2/3( 4x - 2) = 2/3( x - 4) = 8x + 4/ 3 = 2x - 8/ 3 = 8x + 4 = 2x - 8 = 8x - 2x = -8 - 4
- Now that the like terms are grouped probably, you can solve!
- 2/3( 4x - 2) = 2/3( x - 4) = 6x + 4 /3 = 2 + x - 4 /3 =6x + 4 = 2 + x - 4 = 6x + x = 2 - 4 + 4 = 7x = 2 = 7x/7 = 2/7 x = 0.28 2/3( 4x - 2) = 2/3( x - 4) = 6x + 4 /3 = 2 + x - 4 /3 =6x + 4 = 2 + x - 4 = 6x + x = 2 - 4 + 4 = 7x = 2 = 7x/7 = 2/7 x = 0.28 2/3( 4x - 2) = 2/3( x - 4) = 6x + 4 /3 = 2 + x - 4 /3 =6x + 4 = 2 + x - 4 = 6x + x = 2 - 4 + 4 = 7x = 2 = 7x/7 = 2/7 x = 0.28 2/3( 4x - 2) = 2/3( x - 4) = 6x + 4 /3 = 2 + x - 4 /3 =6x + 4 = 2 + x - 4 = 6x + x = 2 - 4 + 4 = 7x = 2 = 7x/7 = 2/7 x = 0.28 2/3( 4x - 2) = 2/3( x - 4) = 6x + 4 /3 = 2 + x - 4 /3 =6x + 4 = 2 + x - 4 = 6x + x = 2 - 4 + 4 = 7x = 2 = 7x/7 = 2/7 x = 0.28 2/3( 4x - 2) = 2/3( x - 4) = 6x + 4 /3 = 2 + x - 4 /3 =6x + 4 = 2 + x - 4 = 6x + x = 2 - 4 + 4 = 7x = 2 = 7x/7 = 2/7 x = 0.28
- 2/3( 4x - 2) = 2/3( x - 4) = 6x + 4 /3 = 2 + x - 4 /3 =6x + 4 = 2 + x - 4 = 6x + x = 2 - 4 + 4 = 7x = 2 = 7x/7 = 2/7 x = 0.28 2/3( 4x - 2) = 2/3( x - 4) = 6x + 4 /3 = 2 + x - 4 /3 =6x + 4 = 2 + x - 4 = 6x + x = 2 - 4 + 4 = 7x = 2 = 7x/7 = 2/7 x = 0.28 2/3( 4x - 2) = 2/3( x - 4) = 8x + 4/ 3 = 2x - 8/ 3 = 8x + 4 = 2x - 8 = 8x - 2x = -8 - 4 = 6x = -12 = 6x/6 = -12/6 x = -2
- WOW
- 2/3( 4x - 2) = 2/3( x - 4) = 6x + 4 /3 = 2 + x - 4 /3 =6x + 4 = 2 + x - 4 = 6x + x = 2 - 4 + 4 = 7x = 2 = 7x/7 = 2/7 x = 0.28 2/3( 4x - 2) = 2/3( x - 4) = 6x + 4 /3 = 2 + x - 4 /3 =6x + 4 = 2 + x - 4 = 6x + x = 2 - 4 + 4 = 7x = 2 = 7x/7 = 2/7 x = 0.28 2/3( 4x - 2) = 2/3( x - 4) = 6x + 4 /3 = 2 + x - 4 /3 =6x + 4 = 2 + x - 4 = 6x + x = 2 - 4 + 4 = 7x = 2 = 7x/7 = 2/7 x = 0.28 2/3( 4x - 2) = 2/3( x - 4) = 6x + 4 /3 = 2 + x - 4 /3 =6x + 4 = 2 + x - 4 = 6x + x = 2 - 4 + 4 = 7x = 2 = 7x/7 = 2/7 x = 0.28 2/3( 4x - 2) = 2/3( x - 4) = 6x + 4 /3 = 2 + x - 4 /3 =6x + 4 = 2 + x - 4 = 6x + x = 2 - 4 + 4 = 7x = 2 = 7x/7 = 2/7 x = 0.28 2/3( 4x - 2) = 2/3( x - 4) = 6x + 4 /3 = 2 + x - 4 /3 =6x + 4 = 2 + x - 4 = 6x + x = 2 - 4 + 4 = 7x = 2 = 7x/7 = 2/7 x = 0.28 2/3( 4x - 2) = 2/3( x - 4) = 6x + 4 /3 = 2 + x - 4 /3 =6x + 4 = 2 + x - 4 = 6x + x = 2 - 4 + 4 = 7x = 2 = 7x/7 = 2/7 x = 0.28 2/3( 4x - 2) = 2/3( x - 4) = 6x + 4 /3 = 2 + x - 4 /3 =6x + 4 = 2 + x - 4 = 6x + x = 2 - 4 + 4 = 7x = 2 = 7x/7 = 2/7 x = 0.28 2/3( 4x - 2) = 2/3( x - 4) = 8x + 4/ 3 = 2x - 8/ 3 = 8x + 4 = 2x - 8 = 8x - 2x = -8 - 4 = 6x = -12 = 6x/6 = -12/6 x = -2
- WOW

More Storyboards By munster1717